If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3y + 6z = 360 Solving 2x + 3y + 6z = 360 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3y' to each side of the equation. 2x + 3y + -3y + 6z = 360 + -3y Combine like terms: 3y + -3y = 0 2x + 0 + 6z = 360 + -3y 2x + 6z = 360 + -3y Add '-6z' to each side of the equation. 2x + 6z + -6z = 360 + -3y + -6z Combine like terms: 6z + -6z = 0 2x + 0 = 360 + -3y + -6z 2x = 360 + -3y + -6z Divide each side by '2'. x = 180 + -1.5y + -3z Simplifying x = 180 + -1.5y + -3z
| 2/3(n−5/6)=21/2 | | 16x^5-44x^4+30x^3= | | 2x+63+7x+18=90 | | 3/4x=9/10 | | 5u+14=3(u+2) | | 6+9x= | | 20-14=g | | 640=5(2)*x | | .75x=1.25x | | 0=-8p-p^2-15 | | X^3-19x-20=0 | | 7(y-4)=9y-40 | | x/5x-40*x*x-8x/7= | | 3(4x+1)=9(2x-1) | | -6n(1+10n)= | | 0=11x-3x^2-10 | | -43=6b+8 | | 125m-100m+38800=40200-175m | | -6(x+3)-12=17+7 | | 1.39=ln(y) | | 6a^2-a-15= | | 2y+1y+15=22 | | 6x=16-x^2 | | 1/3(3.14)(3.5^2)8 | | 6y+2-7y= | | 18-9b=-b^2 | | -14=2(u+8)-7u | | -11u--6u-2u-8=20 | | f(x)=12x-x^3 | | 6.9x-2.1=25.5 | | y-17/19=-719 | | 3k-1-6k=4k+8-9k |